Lactate minimum test during incremental running after a submaximal cycling exercise: a novel test with training applications for triathletes - Vicente-Campous, D.; Barbado, C.; Nunez, M. J.; Chicharro, J. L. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The purpose of the present study was to determine whether running speed determined in a lactate minimum test (lactate minimum intensity, LMI) during a treadmill incremental exercise performed just after submaximal cycling corresponds to the speed of a respiratory exchange ratio of 1.00 (RER-1) and, by extension, to the maximal lactate steady state (MLSS) previously obtained in a standard incremental exercise test.